The logic of scientific and religious principles - Miller, John F. (Sophia, 1973)
In every domain, the philosopher finds some principle which is unfalsifiable in so far as all experience is interpreted in accordance with it. This principle is tautologous or analytic-within-its domain in that it defines fundamental terms with which it characterizes experiences: Newton’s Laws define “mass” and “the equality of times”; the Principle of the Rectilinear Propagation of LIght defines “light”; the Principle of Evolution defines “adaptation” and “natural selection”; and the Principle of the Conservation of Energy defines “a closed system.” Moreover, each principle is employed as a methodological rule or a tacit imperative to the investigator to interpret experience or to draw inferences in accordance with it. Nevertheless, each principle has empirical content: not only by virtue of its place within its respective domain but also because there are sufficient rules of correspondence which make the statement-form empirically relevant; not only because the principle itself is taken to be true but also because empirical inferences are drawn in accordance with it. To construe these principles as mere counterfactuals would be clearly incorrect. Counterfactuals, as Rescher would characterize them, are “belief-contravening suppositions” because certain beliefs are excluded if one is to be consistent. Although this is certainly true of these principles, the range of beliefs contravened is far larger than those beliefs excluded in mere laws of nature. For, to give up these principles would be to give up explaining the entire domain of experience to which they are applicable.